Absorption Laws (Boolean Algebras)

From ProofWiki
Jump to navigation Jump to search

This proof is about Absorption Laws in the context of Boolean Algebra. For other uses, see Absorption Laws.


Let $\struct {S, \vee, \wedge}$ be a Boolean algebra, defined as in Definition 1.

Then for all $a, b \in S$:

$a = a \vee \paren {a \wedge b}$
$a = a \wedge \paren {a \vee b}$

That is, $\vee$ absorbs $\wedge$, and $\wedge$ absorbs $\vee$.


Let $a, b \in S$.


\(\ds a \vee \paren {a \wedge b}\) \(=\) \(\ds \paren {a \wedge \top} \vee \paren {a \wedge b}\) Boolean Algebra: Axiom $(BA_1 \ 3)$: $\top$ is the identity for $\wedge$
\(\ds \) \(=\) \(\ds a \wedge \paren {\top \vee b}\) Boolean Algebra: Axiom $(BA_1 \ 2)$: $\wedge$ distributes over $\vee$
\(\ds \) \(=\) \(\ds a \wedge \top\) Identities of Boolean Algebra also Zeroes
\(\ds \) \(=\) \(\ds a\) Boolean Algebra: Axiom $(BA_1 \ 3)$ $\top$ is the identity for $\wedge$

as desired.


The result:

$a = a \wedge \paren {a \vee b}$

follows from the Duality Principle.